Identification and SNP association analysis of a novel gene in chicken. (8th December 2015) - Mei, Xingxing; Kang, Xiangtao; Liu, Xiaojun; Jia, Lijuan; Li, Hong; Li, Zhuanjian; Jiang, Ruirui
Summary: A novel gene that was predicted to encode a long noncoding RNA (lncRNA) transcript was identified in a previous study that aimed to detect candidate genes related to growth rate differences between Chinese local breed Gushi chickens and Anka broilers. To characterise the biological function of the lncRNA, we cloned and sequenced the complete open reading frame of the gene. We performed quantitative real‐time polymerase chain reaction (qPCR) to analyse the expression patterns of the lncRNA in different tissues of chicken at different development stages. The qPCR data showed that the novel lncRNA gene was expressed extensively, with the highest abundance in spleen and lung and the lowest abundance in pectoralis and leg muscle. Additionally, we identified a single nucleotide polymorphism (SNP) at the 5′‐end of the gene and studied the association between the SNP and chicken growth traits using data from an F2 resource population of Gushi chickens and Anka broilers. The association analysis showed that the SNP was significantly ( P < 0.05) associated with leg muscle weight, chest breadth, sternal length and body weight in chickens at 1 day, 4 weeks and 6 weeks of age. We concluded that the novel lncRNA gene, which we designated pouBW1, may play an important role in regulating chicken growth.